Pengaruh Tata Kelola Perusahaan dan Corporate Social Responbility terhadap Tax Avoidance - Dita Jayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the effect of corporate governance and corporate social responsibility on tax avoidance in IDX companies. The population in the research uses the property and real estate sector on the Indonesia Stock Exchange in 2020 - 2022. The results of this research indicate that corporate governance on independent commissioners, audit committees has an effect on tax avoidance. Meanwhile, corporate governance in institutional ownership has no effect on tax avoidance. And corporate social responsibility has an effect on tax avoidance.